Designing Multi-Cloud Server for Scalable and Secure Sharing Over Web - Timande, Shruti; Dhabliya, Dharmesh (International Journal of Psychosocial Rehabilitation, 2025)
With the internet getting so popular data sharing and security of personal data has gain much more importance than before. Cloud provides and efficient way to outsource the data either online or offline but data security becomes one of the major issues in unreliable multi-cloud environment. This paper addresses the issues in multi-cloud environment and also provides a way to provide better security in multi-cloud environment. Further it discusses the different encryption algorithms that can be used to maintain a design framework for cloud environment.